Triphala Extract Suppresses Proliferation and Induces Apoptosis in Human Colon Cancer Stem Cells via Suppressing c-Myc/Cyclin D1 and Elevation of Bax/Bcl-2 Ratio - Vadde, Ramakrishna (Biomed Res Int, 2015)
Colon cancer is the second leading cause of cancer related deaths in the USA. Cancer stem cells (CSCs) have the ability to drive continued expansion of the population of malignant cells. Therefore, strategies that target CSCs could be effective against colon cancer and in reducing the risk of relapse and metastasis. In this study, we evaluated the antiproliferative and proapoptotic effects of triphala, a widely used formulation in Indian traditional medicine, on HCT116 colon cancer cells and human colon cancer stem cells (HCCSCs). The total phenolic content, antioxidant activity, and phytochemical composition (LC-MS-MS) of methanol extract of triphala (MET) were also measured. We observed that MET contains a variety of phenolics including naringin, quercetin, homoorientin, and isorhamnetin. MET suppressed proliferation independent of p53 status in HCT116 and in HCCSCs. MET also induced p53-independent apoptosis in HCCSCs as indicated by elevated levels of cleaved PARP. Western blotting data suggested that MET suppressed protein levels of c-Myc and cyclin D1, key proteins involved in proliferation, and induced apoptosis through elevation of Bax/Bcl-2 ratio. Furthermore, MET inhibited HCCSCs colony formation, a measure of CSCs self-renewal ability. Anticancer effects of triphala observed in our study warrant future studies to determine its efficacy in vivo.